Pereira diamond: how to measure project economic and social impacts - Pereira, L.; Teixeira, C.; Salgado, A. (International Business Management, 2019)
This research paper presents a model to assist business managers and decision-makers to make better decision of investment projects. This model provides a methodology and principles to assist organizations estimating and evaluating their projects benefits to apply in a Business Case, namely for projects with economic and social impacts. This model may be applied by any organizations (private sector, public sector or NGO) which may aim to leverage business value or generate more social value.